(untitled) - Griffin, Ricky W. (Upper Saddle River, NJ, 2010)
An Overview of International Business; Global Marketplaces and Business Centers; Legal, Technological, and Political Forces; The Role of Culture.; Ethics and Social Responsibility in International Business; International Trade and Investment Theory; International Monetary System and the Balance of Payments; Exchange and International Financial Markets; Formulation of National Trade Policies; International Cooperation among Nations; International Strategic Management; Strategies for Analyzing and Entering Foreign Markets; International Strategic Alliances; International Organization Design and Control; Leadership and Employee Behavior in International Business; International Marketing; International Operations Management; International Financial Management; Human Resource Management and Labor Relations
Keywords: International business enterprises,Hoạt động kinh doanh quốc tế; Management,Quản lý